Response of strawberry (Fragaria × Ananassa Duch.) to PGPR inoculation (Bangladesh Journal of Botany, 2020)
Investigation was carried out to study the effect of Pseudomonas strains on growth, yield and quality of strawberry cv. Chandler. The growth yield and quality of fruits were significantly influenced by various Pseudomonas strains. Root inoculations with selected bacteria significantly increased yield per plant (1.00 - 26.89%) and average fruit weight (0.64 - 11.89%) compared to control. Regarding various physico-chemical characters, viz. TSS, acidity, ascorbic acid and anthocyanin content of fruits, inoculation of Pseudomonas strain CP109 exhibited significantly enhanced values. The results indicated that inoculation with Pseudomonas strains could be an ecofriendly and cost-effective technology for improving the growth, yield and quality of strawberry.